2017
DOI: 10.1017/bec.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Compassion-Focused Therapy for Bulimia Nervosa and Bulimic Presentations: A Preliminary Case Series

Abstract: Objectives: Validated treatments for adults with bulimia nervosa (BN) and related presentations are scarce, and the current most evidenced treatment — cognitive behaviour therapy for eating disorders — is resource intensive and has suboptimal remission rates; there is, therefore, a need to evaluate the effectiveness of other approaches for treating such conditions in routine NHS services. Design: Data from nine patients in an NHS eating disorder service who received compassion-focused therapy (CFT) for BN or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Our findings, with large effect sizes, add to those of previous research, indicating that a compassion‐focused approach may be helpful for individuals with eating difficulties (Gale et al, 2014; Haley et al, 2022; Kelly et al, 2017; Kelly & Carter, 2015; Williams et al, 2017). However, longer‐term follow‐up is required to see whether participants remain in recovery.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings, with large effect sizes, add to those of previous research, indicating that a compassion‐focused approach may be helpful for individuals with eating difficulties (Gale et al, 2014; Haley et al, 2022; Kelly et al, 2017; Kelly & Carter, 2015; Williams et al, 2017). However, longer‐term follow‐up is required to see whether participants remain in recovery.…”
Section: Discussionsupporting
confidence: 81%
“…Kelly and Carter (2015) found a reduction in the weekly binge days and global eating disorder pathology in a sample of 41 individuals with BED who underwent a 3‐week compassion‐based intervention. Williams et al (2017) found a significant improvement in eating psychopathology when delivering individual CFT to eight adults with BN or bulimic presentations. Haley et al (2022) also found a reduction in eating disorder symptoms in women with overweight/obesity and internalized weight bias after a 3‐session self‐compassion intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially developed for people with high levels of shame and self‐criticism (Gilbert & Irons, ). There is emerging evidence for the effectiveness of CFT across range of clinical problems including depression and anxiety (Gilbert & Procter, ; Judge, Cleghorn, McEwan, & Gilbert, ), personality disorder (Lucre & Corten, ), eating disorders (Gale, Gilbert, Read, & Goss, ; Kelly & Carter, ; Williams, Tsivos, Brown, Whitelock, & Sampson, ), psychosis (Braehler et al ., ; Heriot‐Maitland, Vidal, Ball, & Irons, ; Kennedy & Ellerby, ; Laithwaite et al ., ; Mayhew & Gilbert, ), acquired brain injury (Ashworth, Clarke, Jones, Jennings, & Longworth, ; Ashworth, Gracey, & Gilbert, ), and post‐traumatic stress disorder (Au et al ., ; Beaumont, Durkin, McAndrew, & Martin, ; Beaumont, Galpin, & Jenkins, ). However, these studies are primarily pilot/feasibility studies or service evaluations, and hence, the conclusions that can be drawn are limited.…”
Section: Introductionmentioning
confidence: 99%